Efeito de peptídeos angiotensina sobre a sinalização intracelular de células tronco mesenquimais de medula óssea de ratos Wistar - Jousie Michel Pereira (2011)
Objective: The intracellular events stimulated by angiotensin II (Ang II) mediated by MAPKs are associated with proliferation, apoptosis, cell differentiation and vascular contraction. Recent studies suggest that angiotensin-(1-7) (Ang (1-7)) can directly antagonize the intracellular pathways stimulated by Ang II. This study aimed to evaluate the effect of treatment with angiotensin peptides in bone marrow mesenchymal stem cells of Wistar rats on the expression and phosphorylation of MAPKs ERK1/2 and p38. Methodology: The mesenchymal stem cells were isolated from the cultivation of the mononuclear fraction cells obtained from bone marrow of the femur and tibia bones of rats. To confirm the identity of cells, we investigated the presence of positive (collagen I, fibronectin and integrin 1) and negative (CD14 and CD45) markers. The presence of receptor AT1, AT2 and MAS in bone marrow mesenchymal stem cells was investigated using Western Blot and RT-PCR from MAS. The protein extracts from cell cultures previously stimulated with the peptides Ang-(1-7) and Ang II at different concentrations (10-10 - 10-6 mol/L) for 12 hours, were subjected to Western Blot technique using primary antibodies for MAPKs ERK 1/2, phospho p38 and total p38. Results: The presence of AT1, AT2 and MAS in bone marrow mesenchimal cells was documented by Western Blot and RT-PCR from MAS. Treatment with Ang II at concentration of 10-10M stimulated p38 MAPK phosphorilation. Treatment with Ang II at a concentration of 10-8 M induced an increase in ERK1/2 expression, and this effect was reversed by co-treatment with Ang (1-7) at a concentration of 10-7M. Conclusion: These results suggest that Ang(1-7) can negatively modulate Ang II effects in bone marrow mesenchymal stem cells